Bullatacin Triggered ABCB1-Overexpressing Cell Apoptosis via the Mitochondrial-Dependent Pathway. (21st July 2009) - Liang, Yong-Ju; Zhang, Xu; Dai, Chun-Ling; Zhang, Jian-Ye; Yan, Yan-Yan; Zeng, Mu-Sheng; Chen, Li-Ming; Fu, Li-Wu
Abstract : This paper was to explore bullatacin-mediated multidrug-resistant cell apoptosis at extremely low concentration. To investigate its precise mechanisms, the pathway of cell apoptosis induced by bullatacin was examined. Bullatacin causes an upregulation of ROS and a downregulation ofΔ Ψ m in a concentration-dependent manner in ABCB1-overexpressing KBv200 cells. In addition, cleavers of caspase-9, caspase-3, and PARP were observed following the release of cytochrome c from mitochondria after bullatacin treatment. However, neither cleavage of caspase-8 nor change of expression level of bcl-2, bax and Fas was observed by the same treatment. Pretreating KBv200 cells with N-acetylcysteine, an antioxidant modulator, resulted in a significant reduction of ROS generation and cell apoptosis induced by bullatacin. Bullatacin-induced apoptosis was antagonized by z-LEHD-fmk, a caspase-9 inhibitor, but not by z-IETD-fmk, a caspase-8 inhibitor. These implied that apoptosis of KBv200 cells induced by bullatacin was associated with the mitochondria-dependent pathway that was limited to activation of apical caspase-9.